An innovative approach for lid design for rehabilitation of maxillary oncological defect using hollow bulb obturator - Shweta Kumari; Peter John; Ahila Singaravel Chidambaranathan; Muthukumar Balasubramanium (Oral Oncology Reports)
Background: Post Maxillectomy, prosthodontic treatment modalities include surgical obturator, interim obturator and followed by definitive obturator. The surgical and interim obturator serves the purpose of providing a matrix on which surgical packing can be placed, reduces the contamination during wound healing, facilitates speech and permits deglutition and lessens the psychological impact of surgery. Local drug delivery techniques at the surgical site and the fabricated prosthesis have an impact on the targeted tissue. Objectives: To design a hollow bulb obturator with a detachable lid with attachments in the palatal surface of the obturator and to facilitate local drug delivery. Methods: Duplication of patient's maxillectomy cast, pre-shaped plaster bolus was incorporated inside the defect space to create the hollow space. After which a wax pattern was fabricated and acrylized. Wax template of the lid design was made and acrylized incorporating pins. Result: The weight of the prosthesis is reduced. Due to the lesser weight of the prosthesis retention and physiologic function increases. The decrease in pressure to the surrounding tissue aids in deglutition and encourages the regeneration of tissue. The fabricated lid appears stable and retentive, which can be easily removed and placed back according to the need. Conclusion: Local drug delivery techniques at the surgical site and the fabricated prosthesis has an impact on the targeted tissue.The ability of the drug to reach the appropriate anatomic region will always be important, and has been the subject of much research in the past 5 years. Modified hollow bulb of the obturator in this research can aid in local drug delivery in surgical and interim obturators avoiding the removal of the obturator as the whole.